IMPLEMENTASI KEBIJAKAN OPERASIONAL PENINGKATAN PARTISIPASI PRIA DALAM PROGRAM KELUARGA BERENCANA DI KELURAHAN GILINGAN KECAMATAN BANJARSARI KOTA SURAKARTA. - Joko Suranto, Dhian Artika Mahardini (JI@P, 2018)
Mahardini & Suranto, 2018. âImplementation of operational policies inincreasing male participation in Family Planning in Gilingan Sub District,Banjarsari District, City of Surakartaâ. Public Administration, Slamet RiyadiUniversity Surakarta. Theses. Unpublished.This thesis describes the process of implementing operational policies toincrease male participation in Family Planning in Gilingan Sub District,Banjarsari District, City of Surakarta.Implementation of operational policies inincreasing male participation in Family Planning in Gilingan Sub District,Banjarsari District, City of Surakarta uses The Policy Theory of George C.Edward, III, and Van Metter & Van Horn, which are: 1) Communication, 2)Resources, 3) Disposition, 4) Structure of Bureaucracy, 5) Dimension andPurpose of Policy, 6) Economy, Social, and Cultural Conditions.Regulation ofThe Minister for Women Empowerment/ Head of BKKBN No. 70/ HK-010/B5/2001 on Organization and Working Procedure of National FamilyPlanning Coordinating Agency (BKKBN) Province and Regency/Cityregulates forming a Male Participatory Increase Section under the Division ofFamily Planning and Health Reproduction Control. This section is in chargeof preparing socially adaptable information packages, also preparing anddeveloping target segmentation to increase Family Planning maleparticipants. The implementation in subdistricts/villages and districts will beconducted by PLKBs (Family Planning Field Instructors) and PKBs (FamilyPlanning Instructors) and their respective Coordinators.ResearchMethodology being used is qualitative descriptive. Data collecting techniqueuses interviews and documentations. Data analysis techniques used isInteractive Analysis Model (Miles and Huberman). The conclusions of thisstudy are: 1) Communication aspect: presence of several socializations,there is consistency and clarity between socializations, and instructors areable to cooperate with related parties and to use many publication andpromotion medias. 2) Resources aspect: availability of good quality humanresource that is the instructors, resource availability of government budget,resource availability of equipment and tools, resource availability ofauthorized programme. 3) Disposition aspect: presence of positiveperception from the PLKBs and PKBs, existence of real and concreteservices from the instructors. 4) Structure of Organization aspect:organizational structure is already formed, roles and responsibilities isalready distributed. 5) Dimension and Purpose of Policy aspect: compatibilitybetween Family Planning and the purpose of bureaucratic reform that isimplementing clean government and good governance. 6) Economy, Social,and Cultural Conditions aspect: presence of support from Sub Districtofficials and related agencies, also conducive community situation inimplementing this policy.Keywords: Implementation, Policy, Operational, Participation